Serum levels of GDF-15, betatrophin, TNF-? and IL-6 in diabetic patients with and without diabetic complications - Yilmaz, Ahmet; Kaymaz, Tugce; Yakar, Burkay; Gomleksiz, Mehtap; Onalan, Erhan; Gursu, Mehmet F. (Saudi Med J, 2025)
Objectives: To investigate serum levels of growth differentiation factor 15 (GDF-15), inflammatory biomarkers, and betatrophin in individuals with diabetes mellitus, both with and without complications. Methods: A cross-sectional analysis was conducted involving patients with diabetes. Participants were categorized into 3 groups: Group 1 (30 healthy individuals without diabetes), Group 2 (30 diabetic patients without complications), and Group 3 (30 diabetic patients with complications). Blood samples were collected to assess standard biochemical parameters, as well as plasma concentrations of betatrophin, tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6), and GDF-15. All serum biomarkers were quantified using enzyme-linked immunosorbent assay (ELISA) techniques. Results: Median GDF-15 concentrations were 486.96 pg/mL (range: 172.2-1272.0) in the control group, 843.9 pg/mL (range: 458.3-1393.3) in diabetics without complications, and 1794.3 pg/mL (range: 741.6-4449.5) in those with complications. The GDF-15 levels were significantly elevated in diabetic patients compared to healthy controls (p<0.001), and markedly higher in patients with complications than those without (p<0.001). Additionally, TNF-alpha, IL-6, and betatrophin levels were significantly increased in diabetic individuals relative to the control group (all p<0.001). Conclusion: Serum GDF-15 levels are elevated in diabetic patients compared to non-diabetic controls and are further increased in those with complications. These findings suggest that GDF-15 may serve as a potential biomarker for diabetes severity and complication risk.
Keywords: Growth Differentiation Factor 15; Diabetes Complications; Angiopoietin-Like Protein; Inflammation; Diabetes Mellitus